A 9.38-bit, 422nW, high linear SAR-ADC for wireless implantable system - Silpa Kesav Velagaleti; Nayanathara K. S.; Madhavi B. K. (Universitas Ahmad Dahlan, 2021)
In wireless implantable systems (WIS) low power consumption and linearity are the most prominent performance metrics in data acquisition systems. successive approximation register-analog to digital converter (SAR-ADC) is used for data processing in WIS. In this research work, a 10-bit low power high linear SAR-ADC has been designed for WIS. The proposed SAR-ADC architecture is designed using the sample and hold (S/H) circuit consisting of a bootstrap circuit with a dummy switch. This SAR-ADC has a dynamic latch comparator, a split capacitance digital to analog converter (SC-DAC) with mismatch calibration, and a SAR using D-flipflop. This architecture is designed in 45 nm CMOS technology. This ADC reduces non-linearity errors and improve the output voltage swing due to the usage of a clock booster and dummy switch in the sample and hold. The calculated outcomes of the proposed SAR ADC display that with on-chip calibration an ENOB of 9.38 (bits), spurious free distortion ratio (SFDR) of 58.621 dB, and ± 0.2 LSB DNL and ± 0.4LSB INL after calibration.